Introduction to Electronics, An. - Saxena, A. K. (Alpha Science International, 2014)
AN INTRODUCTION TO ELECTRONICS covers the syllabus of B. Sc. Electronics, and is divided into twelve chapters viz. circuit analysis (network analysis and network theorems) semiconductors and semiconductor diodes, clippers and clampers, two terminal devices (rectifiers Zener, varactor and tunnel diodes, photodiode, LED and solar cell). Bipolar Junction Transistors (CE, CB, and CC configurations), Amplifiers two port networks, h-parameters and CE, CB, CC and RC coupled amplifiers, feedback in amplifiers, types of feedback sinusoidal oscillators (Colpitt, Hartley phase-shift and Wien bridge oscill.